A phase 2 study of ibrutinib in combination with bortezomib and dexamethasone in patients with relapsed/refractory multiple myeloma. (7th March 2020) - Hajek, Roman; Pour, Ludek; Ozcan, Muhit; Martin Sánchez, Jesus; García Sanz, Ramon; Anagnostopoulos, Achilles; Oriol, Albert; Cascavilla, Nicola; Terjung, Andreas; Lee, Yihua; Briso, Eva M.; Dobkowska, Edyta; et al.
Abstract: Objective: We evaluated ibrutinib, a once‐daily inhibitor of Bruton's tyrosine kinase, combined with bortezomib and dexamethasone in patients with relapsed or relapsed/refractory multiple myeloma who had received 1‐3 prior therapies. Methods: This was a phase 2, single‐arm, open‐label, multicentre study (NCT02902965). The primary endpoint was progression‐free survival (PFS). Results: Seventy‐six patients were enrolled; 74 received ≥1 dose of study treatment. After median follow‐up of 19.6 months, median PFS was 8.5 months (95% CI: 6.2‐10.8); median overall survival was not reached. Overall response rate was 57% (95% CI: 45‐68), and median duration of response was 9.5 months (95% CI: 6.9‐10.6). Grade 3/4 AEs occurred in 73% of patients and fatal AEs occurred in 15% of patients. Incidence of major haemorrhage was 5%; one patient died from cerebral haemorrhage. After an observed increased incidence of serious (42%) and fatal (11%) infections, enrolment was suspended to implement risk‐minimisation measures. The safety profile was otherwise consistent with known safety profiles of the individual drugs. Conclusion: Ibrutinib combined with bortezomib and dexamethasone elicited clinical responses. However, efficacy assessments conducted at potential restart of enrolment indicated that the targeted PFS could not be reached with additional patient enrolment, and the study was terminated.